Family study of manipulation tactics - Butković, Ana (Array, 2007)
The aim of this study was to explore the aetiology of individual di.erences in manipulation tactics and the relationship between manipulation tactics and personality traits using a family study design. The sample used in the study consisted of 193 (60 male, 133 female) pupils of high-schools in Zagreb and their parents (152 male, 188 emale). All participants completed a new instrument assessing manipulation tactics, as well as the NEO-Five Factor Inventory (NEO-FFI) to assess personality. Data were collected so that both selfreports and observer-reports of manipulation tactics and personality traits were available. Two measures of parent– child similarity in anipulation tactics were calculated: correlations between ingle parent and offspring, and midparent– offspring regressions. Both measures indicate that there is a familial aggregation of manipulation tactics. The relationship between personality traits and manipulation tactics was tested in correlation and regression analyses. Although both analyses showed coherent links between personality traits and manipulation tactics (e.g. low Agreeableness and high euroticism were associated with higher use of manipulation tactics), results also indicate that personality traits play a marginal role in election and use of manipulation tactics.